(untitled) (East West Medical College Journal, 2025)
Introduction: Acute cholecystitis has become a fairly common disease in this modern era due to overblown culture of first food chain shops in Bangladesh in the last decade or two. Laparoscopic cholecystectomy is the gold standard treatment of such cases. The traditional method was if 72 hours have elapsed from the onset of symptoms, either conservative treatment was provided or proceed to open cholecystectomy if conservative treatment failed. But now-a-days, due to advancement in the safety measures, instruments and expertise, laparoscopic cholecystectomy is the treatment of choice. In our East West Medical College Hospital we routinely go for laparoscopic cholecystectomy in such cases. Materials and Methods: This is an observational study done in East West Medical College Hospital from January 2022 to December 2024. Total of 355 patients were admitted for laparoscopic cholecystectomy; among them 132 cases with acute cholecystitis and/ or it’s complications. Results: During this study, 132 cases were admitted with acute cholecystitis and all of them underwent laparoscopic cholecystectomy. Among them 126 cases were completed laparoscopically despite per-operative difficulties in quite a few cases. Only 6 cases needed conversion to open (p value 0.045). Conclusion: In experienced hand and with adequate expertise, in acute cholecystitis cases laparoscopic cholecystectomy is a safer option than conservative despite elapsing 72 hours of onset of presentation. EWMCJ Vol. 13, No. 2, July 2025: 103-108